Penerapan Data Mining Dengan Menggunakan Algoritma Ct-Pro Untuk Korelasi Obat - Septianti Ari Mindawati Hasibuan; Berto Nadeak (JURIKOM (Jurnal Riset Komputer), 2018)
A very large set of transaction data is only stored in the database and less utilized. Sales data can be further processed to obtain new information. For example, from the information can be seen simultaneously provided drugs. Such knowledge can be used as marketing complementary products and make monster sold in Apotek Kimi Farma. Data mining technology as a solution for customers. Marketing strategy and advice between strategies that can be supported by consumers. With the problems that exist in Apotik Kima Farma, the researchers tried to provide an alternative by applying the CT-Pro Algorithm. This algorithm is a market basket analysis algorithm used to produce association rules, with the "if-then" or "if-then" pattern. Market basket analysis is one of the techniques of data mining that uses patterns in a time. The purpose of this use can help the pharmacist to know the improvement of complementary drugs obat.dengan utilize drug sales transactions with patients.